Retrospective cohort study analyzing temporal bone cortical thickness and perioperative complication rate, in pediatric cochlear implantation - Markodimitraki, Laura M.; Dankbaar, Jan W.; Stegeman, Inge; Thomeer, Hans G. X. M. (Frontiers in Pediatrics, 2025)
BackgroundCochlear implant fixation in pediatric patients can be challenging due to the thin cranial bone. The dura matter can be exposed by drilling a bony recess leading to possible complications. A minimally invasive newer fixation method might avoid such risks.ObjectivesThe study focus is to assess the feasibility of drilling a bony well adequate for cochlear implant receiver/stimulator device embedment in pediatric patients of different age groups. We also aim report the occurred complications and device failure rates using different surgical techniques for cochlear approach and fixation of the implant.MethodsComputed tomography (CT) scans of 96 pediatric patients (192 ears) were acquired. An optimal location was found within a predetermined area of the temporal bone, using an in-house designed algorithm in Materialise Python API. The feasibility of drilling a bony well was assessed by digitally removing a ramped shaped bony well. Skull thickness descriptive data were calculated, before and after the removal of the bone. Clinical data of pediatric CI patients receiving their cochlear implant between 1996 and 2021 in our tertiary center, were retrospectively collected.ResultsIn 153 ears (79.7%) it was not feasible to create a bony well without exposing the dura mater. In young children aged 0-4 years, drilling a bony well was not feasible in almost all patients (n=69, 98.6%). Mean minimum bone thickness of the location determined by the algorithm, in different age groups, varied from 1.84 mm in the 0-4 years, to 3.31 mm in the 15-17 years age group. We included 344 cochlear implants in 230 patients with a mean age of 3 years. Most implants were placed using the mastoidectomy with posterior tympanotomy (MPTA) approach technique (n=256, 74.4%) and fixated with the bony well fixation technique with or without bony tie-down sutures (n=293, 85.1%). Major complications occurred in all surgical techniques groups. Device related complications occurred in both the bony well and the tight pocket groups.ConclusionDrilling a bony well for fixation of the cochlear implant without exposing the dura matter is not feaible in children. No difference in complication rates was reported regarding device failure between subgroups.